Inferior Muscularity of the Rectus Femoris to Vasti in Varsity Oarsmen - Ema, R.; Wakahara, T.; Kanehisa, H.; Kawakami, Y. (International Journal of Sports Medicine, 2014)
The purpose of this study was to examine the morphological profiles of 4 constituents (vastus lateralis, vastus medialis, vastus intermedius and rectus femoris) of the quadriceps femoris in oarsmen through comparison with non-athletes. T1-weigheted magnetic resonance (MR) images of the thigh were obtained from 14 oarsmen and 19 non-athlete men. From the MR images, serial anatomical cross-sectional areas (ACSAs) and muscle volume of each muscle were determined. The muscle volume of the total quadriceps femoris, vastus lateralis, vastus medialis and vastus intermedius were significantly larger in the oarsmen than in the non-athlete men, whereas that of the rectus femoris was comparable for the 2 groups. The portion of the rectus femoris as a percentage of total quadriceps femoris volume was significantly higher in the non-athlete men than in the oarsmen, and vice versa for the vastus lateralis. The proximal-to-distal and middle-to-distal ACSA ratios in each muscle did not differ between the 2 groups. The present results indicate inferior muscular hypertrophy of the rectus femoris compared to the vasti in oarsmen, and that the vasti are equally hypertrophied along their lengths. This may be due to muscle-specific adaptation to the rowing exercise.
Keywords: quadriceps femoris; inter-muscle difference; muscle volume; cross-sectional area; magnetic resonance image; rower